Antineoplastic drugs : organic syntheses - Lednicer, Daniel, 1929- (Chichester, West Sussex : John Wiley & Sons. Ltd, 2015)
"Antineoplastic Drugs: Organic Syntheses is written to appeal to organic and medicinal chemists in industry and academia. It is beneficial to those composing grant proposals for NCI and related organizations"--
9.2.3 Proteasome Inhibitors9.2.4 PARP Inhibitors; 9.2.5 Various Other Enzyme Inhibitors; References; Chapter 10 Miscellaneous Antineoplastic Agents; 10.1 Acyclic; 10.2 Monocyclic; 10.3 Two Linked Rings; 10.4 Rings on a Chain; 10.4.1 Two Rings; 10.4.2 Four and More Rings; 10.5 Fused Rings; 10.5.1 Indoles; 10.5.2 Purine-Like; 10.5.3 Tetralins and a Naphthalene; 10.5.4 Etc.; References; Appendix A; Index of Heterocycle Syntheses; Subject Index; EULA.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Antineoplastic agents; Drugs -- Synthesis; Antimetabolites; Antineoplastic agents; Cancer; Drugs -- Administration; Pharmacognosy; SCIENCE -- Life Sciences -- Biochemistry; Antineoplastic agents; Drugs -- Synthesis; Electronic books